IDENTIFICATION OF RISK TRIGGERS ON PRODUCTION ACTIVITIES IN ASPHALT MIXING PLANT UNIT SUPPLY CHAINS IN BALI - A.A.A Made Cahaya Wardani; I Nyoman Arya Thanaya; Nyoman Yudha Astana; A.A. Gde Agung Yana (Journal of International Conference Proceedings (JICP), 2019)
Implementation of the project’s time, cost and quality is the goal to be achieved in each project. The characteristics of construction are different for each project, wich the risks found in all stages of the success of the project when each risk faced at each stage of the work can be handled properly. One of the risks in the project stage is risk in supply chain management. Supply chain risk needs to be handled well so that short-term project operations can be achieved. Likewise in the Road Infrastructure Development in Bali Province which certainly faces many obstacles, one of which is the risk in the concrete asphalt supply chain produced by the AMP unit. For this purpose, activities in the AMP process will be identified which can pose a risk. After knowing the risks that occur, mitigation measures will be carried out to prevent and to minimize the risk. To find out the risks faced by the AMP supply chain, it is necessary to first identify activities in the production process that can pose a risk. This study is a collection of literature studies and interviews with competent parties in the field of AMP production processes, namely operators, management and leaders of the AMP Production unit. From the results of research on AMP production processes identified as a field of manufacturing industry that produces hot asphalt used in infrastructure projects in Bali. This research was conducted at the AMP unit found in Bali. From research, the production process and AMP business are based on Supply, Input, Process, Output and Customer activities. (SIPOC). After the activities contained in the Asphalt production process, it is known that further risks can be identified.